2016
DOI: 10.1016/j.ajic.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Point of care hand hygiene—where's the rub? A survey of US and Canadian health care workers' knowledge, attitudes, and practices

Abstract: This survey demonstrates that similarities between Canada and the United States were more common than not, and the survey raises, or suggests, potential knowledge gaps that require further illumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 11 publications
2
37
0
2
Order By: Relevance
“…1,2 However, HH performance among HCWs was reported to be as low as about 38%. 1,6 Therefore, infection control activities focus primarily on enhancing the HH performance of HCWs; various kinds of infection control activities for HH, such as education, monitoring, and feedback, and a convenient supply of HH products, have been recommended and implemented. 1,3,5 The recommended ratio of infection control nurses (ICNs) was 0.8-1.0 ICN per 100 beds in 2002 7 to 1.2 ICN per 100 beds in 2014 8 in an acute care hospital, because ICNs are key persons to successfully decrease HAIs by managing and developing infection control activities.…”
mentioning
confidence: 99%
“…1,2 However, HH performance among HCWs was reported to be as low as about 38%. 1,6 Therefore, infection control activities focus primarily on enhancing the HH performance of HCWs; various kinds of infection control activities for HH, such as education, monitoring, and feedback, and a convenient supply of HH products, have been recommended and implemented. 1,3,5 The recommended ratio of infection control nurses (ICNs) was 0.8-1.0 ICN per 100 beds in 2002 7 to 1.2 ICN per 100 beds in 2014 8 in an acute care hospital, because ICNs are key persons to successfully decrease HAIs by managing and developing infection control activities.…”
mentioning
confidence: 99%
“…With respect to healthcare professionals' adherence to use this type of HH procedure, some international studies indicate an increasing trend in using ABH in practice (3)(4) . However, in other studies, including Canadian Overall, respondents indicated a statistically significant preference for soap and water over ABH (4) . The reasons for this choice vary and include the feeling that hands are clean after using soap and water in HH, low tolerance of the alcohol-based product offered by the institution, lack of knowledge/training, behavioral and cultural factors, and institutional safety culture (1,4,(6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…This recommendation was made because healthcare workers are prone to skin disease for many reasons, frequent hand washing is one of them and allergic contact dermatitis due to alcohol-based handrubs is not very common. ABH causes less skin dryness, requires only approximately one third of the time to perform, and is more effective in eliminating microorganisms, relative to soap and water, when the hands are visibly clean (1,4) . Other measures should be considered to reduce the risk of developing occupational skin disease as using gloves only for as long as necessary; washing visibly soiled hands with soap and water; and applying moisturizer mainly at the end of the day (1,(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations